Spt2p defines a new transcription-dependent gross chromosomal rearrangement pathway. - Nilabja Sikdar; Soma Banerjee; Han Zhang; Stephanie Smith; Kyungjae Myung (PLoS Genetics)
Large numbers of gross chromosomal rearrangements (GCRs) are frequently observed in many cancers. High mobility group 1 (HMG1) protein is a non-histone DNA-binding protein and is highly expressed in different types of tumors. The high expression of HMG1 could alter DNA structure resulting in GCRs. Spt2p is a non-histone DNA binding protein in Saccharomyces cerevisiae and shares homology with mammalian HMG1 protein. We found that Spt2p overexpression enhances GCRs dependent on proteins for transcription elongation and polyadenylation. Excess Spt2p increases the number of cells in S phase and the amount of single-stranded DNA (ssDNA) that might be susceptible to cause DNA damage and GCR. Consistently, RNase H expression, which reduces levels of ssDNA, decreased GCRs in cells expressing high level of Spt2p. Lastly, high transcription in the chromosome V, the location at which GCR is monitored, also enhanced GCR formation. We propose a new pathway for GCR where DNA intermediates formed during transcription can lead to genomic instability.